Role of hair pigmentation in drug incorporation into hair. (December 2017) - Yu, Hyerim; Jang, Won-Jun; Jang, Jung-Hee; Park, Byoungduck; Seo, Young Ho; Jeong, Chul-Ho; Lee, Sooyeun
Highlights: The role of hair pigmentation in drug incorporation into hair was investigated. Rats carrying hair with different melanin status were used. Human cells representing the main pigmentary unit in hair were used. Hair pigmentation is a facilitating factor for the incorporation of basic compounds. The cell study provided insight into the drug incorporation process into hair. Abstract: Hair analysis has notably expanded its application as a bio-monitor for drug or toxicant exposure. Hair pigmentation is proposed as a major factor affecting drug incorporation into hair; however, the mechanisms underlying the incorporation of drugs into hair are still unclear. In the present study, the effect of hair pigmentation on drug incorporation into hair was examined using rats carrying hair with different melanin status and human cells (SK-Mel-28 cells, HaCaT cells and the co-cultured HaCaT cells with SK-Mel-28 cells) representing the main pigmentary unit in hair. Tramadol, a synthetic opioid analgesic, was selected as a model drug. The distribution of tramadol and its phase I ( O -desmethyltramadol [ODMT], N -desmethyltramadol [NDMT] and N, O -didesmethyltramadol [NODMT]) and phase II metabolites (ODMT-glucuronide and NODMT-glucuronide) was investigated in non-pigmented and pigmented hair from Long–Evans rats. Moreover, the incorporation levels of ODMT and ODMT-glucuronide were compared in hair cells. The concentrations of tramadol and its phase I metabolites were significantly higher in pigmented rat hair while those of phase II metabolites did not showed any consistent significant difference depending on the status of hair pigmentation. ODMT was taken up to a greater extent than ODMT-glucuronide by SK-Mel-28 cells, HaCaT cells and the co-cultured HaCaT cells with SK-Mel-28 cells. Notably, the incorporated level of ODMT was higher in SK-Mel-28 cells than HaCaT cells and the concentration difference of ODMT was significantly larger than that of ODMT-glucuronide. This study clearly demonstrated that hair pigmentation played a role as a facilitating factor for the incorporation of basic compounds and provided insight into the drug incorporation process into hair.